Bone metabolism disorder in epileptic children - Nakhaey Moghadam, Maryam; Teimouri, Alireza; Khajeh, Ali; Hoseini, Seiide bahare (Iranian Journal of Child Neurology, 2018)
Background and Objective: There are frequent anti-epileptic drugs which are used in management of epilepsy. Anti-epileptic drugs may have some complications on bone and vitamin-D metabolism. In this study we aimed to Comparison of Bone metabolism disorder in epileptic children with health child in zahedan Methods: This case-control study was performed on bone metabolism disorder in epileptic children. Forty epileptic children was enetered to the study based on accessability scheme and 40 participants randomly selected for control group from those who were referred to the centers for rutine check up. Blood samples were collected from all participants to assess serum calcium, phosphorus, PTH, magnesium, vitamin D, calcium urine, serum albumin, creatinine random urine. Statistical analyses were performed using SPSS software. Results: Of 40 epileptic children 23 (57.5%) and 17 (42.5%) were male and female respectively. The prevalence of low vitamin D was 37.5% for patients compared to 12.5% for controls (chi-square = 6.667 and p= 0.010). Of 80 participants, 15 individuals had abnormal PTH level which is distributed of 2 and 13 for patients and control groups respectively (chi-square = 9.928 and p= 0.002). In the cases of Ca and Mg their levels were similar in both patients and controls. The status of the parameters in the classification of normal and abnormal assessed based on number of medications intake resulted that number of medications intake had not effect on the parameters status. Conclusion: our study, like previous studies showed that in epileptic children, frequency of hyperparathyroidy and vitamin D deficiency increased.